Older people and their use of mobile devices: issues, purpose and context - Abd Malik, Sofianiza; Azuddin, Muna; Abdullah, Lili Marziana; Mahmud, Murni (Institute of Electrical and Electronics Engineers Inc., 2014)
Today, the use of mobile devices has increased tremendously in all aspects of daily life. It has also provided older people with better means of communication, which allows them to connect with their family and social groups. However, they face challenges in using mobile devices due to their age-related physical limitations and unfamiliarity of various mobile device designs. This preliminary study was conducted to understand the older people’s experiences in using mobile devices and their applications, in which a survey and a discussion had been carried out among the older users. Findings indicated that older people were aware of its technological benefits, but they faced issues related to the variety of mobile device designs and also motivational factors that prevented them from fully utilising the devices.